Effects of virtual reality simulation on medical students’ emotional and subjective experience compared to high-fidelity simulation in pediatrics clerkship - Sejin Kim; Jang Hoon Lee; Hyun Joo Jung; Mira Kim; Su Kyung Lee; Jihye Yu (PLoS ONE, 2025)
This study aimed to explore the educational impact of virtual reality (VR) simulation compared to high-fidelity (HF) simulation. Recently, VR simulation has been integrated into medical education, offering advantages such as cost- and space-efficiency, accessibility, and autonomy, enabling self-directed, repeated practice. Prior research comparing VR and HF simulations has focused primarily on knowledge acquisition, skill development, and learner satisfaction. Given that medical students often experience low confidence and high anxiety during clinical transitions, it is essential to examine the VR simulation’s impact on these emotional factors and students’ subjective experiences. This study investigated the effects of VR and HF simulations on anxiety, confidence, engagement, and perceived learning using multiple-item self-report scales. Data were analyzed using independent t-tests to compare the two simulation methods. The study included 40 fifth-year Korean medical students in a pediatric clerkship. Participants completed both VR and HF simulations, followed by a questionnaire assessing these variables. Results showed no statistically significant differences between VR and HF simulations across the measured domains. However, item-level analysis indicated slightly higher anxiety in VR simulation but greater perceived learning in cognitive domain, suggesting that VR may be more beneficial for cognitive learning compared to HF simulation. As VR simulation has only recently been incorporated into medical education, this study represents a first attempt to compare its impact with that of HF simulation focusing on subjective outcomes. Although no significant differences were found, the cost and space efficiency of VR simulation along with its support for autonomous learning underscore the need for further research, particularly on students’ experiences, and learning objectives.